2018
DOI: 10.1093/jxb/ery230
|View full text |Cite
|
Sign up to set email alerts
|

Sector analysis reveals patterns of cambium differentiation in poplar stems

Abstract: Sector analysis in poplar tree stems was used to shed light on cell identity, cell fate, and patterns of development within the vascular cambium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 50 publications
2
34
0
1
Order By: Relevance
“…Ключевым моментом приобретения автономности фитомером является, согласно рассматриваемой ранее гипотезы (Степанов, 2016), образование клеток склеренхимы в виде волокон, как это наблюдается первоначально у Populus nervirubens или же склереид, что отмечено у Quercus robur L. (Галеновская, Кондратьева-Мельвиль, 1971). В дальнейшем, по мере развития фитомера за счёт новообразования веретеновидным и лучевым камбием клеток ксилемы и флоэмы (Bossinger, Spokevicius, 2018) происходит усиление интеграции с клетками сердцевины и коры стебля, включая, как это наблюдалось у P. nervirubens, образование в лучевой паренхиме флоэмы волокнистых склереид, связанных с волокнами склеренхимы. Кроме этого, образуются дополнительные группы склереид в мягком лубе (рис.…”
Section: рисunclassified
“…Ключевым моментом приобретения автономности фитомером является, согласно рассматриваемой ранее гипотезы (Степанов, 2016), образование клеток склеренхимы в виде волокон, как это наблюдается первоначально у Populus nervirubens или же склереид, что отмечено у Quercus robur L. (Галеновская, Кондратьева-Мельвиль, 1971). В дальнейшем, по мере развития фитомера за счёт новообразования веретеновидным и лучевым камбием клеток ксилемы и флоэмы (Bossinger, Spokevicius, 2018) происходит усиление интеграции с клетками сердцевины и коры стебля, включая, как это наблюдалось у P. nervirubens, образование в лучевой паренхиме флоэмы волокнистых склереид, связанных с волокнами склеренхимы. Кроме этого, образуются дополнительные группы склереид в мягком лубе (рис.…”
Section: рисunclassified
“…In a tree trunk during the active growth season, the cambial zone is composed of several layers of thin-walled cells that appear alike in histological cross-sections (Figure 5A). Recently, Bossinger et al [99] performed an interesting somatic sector analysis in the Populus stem, suggesting the existence of a single cell layer of cambial initials, thought of as stem cells, that can divide in both anticlinal and periclinal orientations, and independently give rise to xylem or phloem. With their system, the authors succeeded in visualizing cell fate during wood development deep inside the trunk over the course of several months, providing insight into the cambial dynamics in a mature tree trunk.…”
Section: Agronomically Important Structures Derived From Plant Vasmentioning
confidence: 99%
“…After cambial initials divide, they enter the differentiation zone, forming either xylem or phloem mother cells and, in turn, xylem or phloem. Bossinger and Spokevicius (2018) used sector analysis to determine that cambial initials originate from a single layer of cells, adding compelling evidence to a 120-year debate.…”
Section: Populus Wood and The Importance Of Secondary Growthmentioning
confidence: 99%
“…The research by Bossinger and Spokevicius (2018) not only answers basic questions about cambial meristem cell fate and differentiation in Populus , but also provides a standard framework of wild-type cell differentiation in the tree stem. In our own research using activation tagged Populus ( Harrison et al , 2007 ), we have identified several mutants with alterations in wood development including the ratio of xylem to phloem, wood biomass (which is increased) and altered wood properties such as lignin content.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation